1970
DOI: 10.4314/ejhs.v29i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Pattern and Its Association with Glycaemic and Blood Pressure Control among People Living with Diabetes (PLWD) In The Ho Municipality, Ghana

Abstract: BACKGROUND: Physical activity (PA) offers considerable health benefits for diabetic patients. However, extensive high levels of inactivity has been reported among diabetic patients. This study sought to assess the patterns of physical activity and its relationship with two management-relevant outcomes (glycaemic and blood pressure control)among people living with diabetes in the Ho Municipality, Ghana.METHODS: A hospital-based cross-sectional study was carried out from January 2017 to April 2017 among 150 purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 35 publications
3
18
0
Order By: Relevance
“…Of the 21 studies, 5 were from South Africa [ 41 45 ], 5 from Ethiopia [ 10 , 46 – 49 ], 3 from Kenya [ 50 52 ], 2 from Tanzania [ 53 , 54 ], 2 from Nigeria [ 55 , 56 ], and 1 from Cameron [ 24 ], Uganda [ 57 ], Botswana [ 58 ], and Ghana [ 59 ]. All studies were institution-based cross-sectional studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 21 studies, 5 were from South Africa [ 41 45 ], 5 from Ethiopia [ 10 , 46 – 49 ], 3 from Kenya [ 50 52 ], 2 from Tanzania [ 53 , 54 ], 2 from Nigeria [ 55 , 56 ], and 1 from Cameron [ 24 ], Uganda [ 57 ], Botswana [ 58 ], and Ghana [ 59 ]. All studies were institution-based cross-sectional studies.…”
Section: Resultsmentioning
confidence: 99%
“…All studies were institution-based cross-sectional studies. To define suboptimal blood pressure control, BP cut point of ≥ 140/90 was used by 11 studies [ 10 , 42 , 45 47 , 49 , 52 , 56 , 58 , 60 , 61 ], ≥ 140/80 by 3 studies [ 44 , 57 ], and ≥ 130/80 by 7 studies [ 24 , 43 , 51 , 53 – 55 ] (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…33 Moreover, there are possible mechanisms concerning the relationship of RHGS and hypertension with physical activity; primarily, the inverse association between exercise and physical activity with hypertension and muscle strength is the result of strength training. 29,34 Second, isometric handgrip exercises improve the structure of the brachial artery. 35,36 Therefore, low HGS can be associated with poor conditions of the brachial artery, which can lead to hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from studies buttress the fact that medication adherence facilitates glycaemic control. The studies by Alqami & Osei-Yeboah et al [47,48] found an association between glycaemic control and medication adherence. These studies demonstrate the importance of medication adherence even in the elderly diabetic patient.…”
Section: Discussionmentioning
confidence: 98%